A conceptual framework of e-loyalty in social-based e-commerce. (2017) - Alhijawi, Bushra; Douglass, Hourya
The social-based e-commerce as we named is a type of e-commerce, which appeared as a result of widespread use of social networks like Facebook, Instagram, YouTube, and Twitter. The retailer in social-based e-commerce depends on the personal profile, pages, or groups on the social networks to present their products. In this study, we investigate the factors that affect the customer satisfaction and e-loyalty in this type of e-commerce. Four factors are proposed (i.e., usefulness, usability, customer services, and customisation) that may have an impact on customer satisfaction and may derive the e-loyalty in social-based e-commerce. Online survey was distributed and 95 complete and valid questionnaires were returned. All the four factors have a positive impact on customer satisfaction. In addition, the customer satisfaction has a positive impact on e-loyalty in social-based e-commerce. The findings suggest that to determine e-satisfaction in SEC, the merchants need to focus on providing a handmade, tailor-made, variant colours and sizes products, special attention by the salespersons and deliverymen to the customers. This will reflect on the loyalty of the customers.